The influence law of process parammeters on end concavity of hexahedral blank cross wedge rolling (CWR) - Y. Chang; X. D. Shu; T. Z. Chen (Metalurgija, 2020)
In order to expand the range of the cross wedge rolling (CWR) product, realize CWR of hexahedral blank. In this paper, the three-dimensional Finite element model (FEM) of hexahedral blank CWR is established by DEFORM finite element software. The influence of forming angle, spreading angle and section shrinkage on the length of concavity is analyzed, compared with the round billet rolling results under the same parameters, the concavity length of the hexahedral blank is slightly larger than that of round billet, and the influence of process parameters on the concavity is basically the same. The research results provide theoretical guidance for the rational determination of process parameters for CWR of hexahedral blank.